On the Realization of the Contractual Penalty Agreement Concluded in the Form of a Notarial Record - Radovanović, Sanja M.; Miščević, Nikolina B. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
Abstract: In a contractual penalty agreement the debtor obliges to pay a certain amount of money to the creditor or to provide him with some other material benefit if he fails to fulfill the main obligation, or if he fails to fulfill it in a timely manner. It is indisputable in the domestic legal theory that a contractual penalty is an accessory right in relation to a claim whose security it serves, but the extent of its accessoriness is arguable. Authors in this paper analyze the accessoriness of the contractual penalty in the domain of realization, i.e. the question of possible claim for payment of the contractual penalty, irrespective of the requirement for compulsory settlement of the main claim. This issue becomes complex in the case of contractual penalties for delay in performance, when the creditor has not yet received, nor demanded fulfillment of the main obligation. Therefore, the authors try to answer the above question in context of the possibility of concluding a contractual penalty agreement in the form of an executive notarial record and the possible compulsory settlement of the claim for a contractual penalty on the basis of this enforceable title.